137k views
5 votes
14. Solve the Quadratic equation by the
method of completing square 3x2 - 8x - 3 ​

User Revital
by
5.3k points

1 Answer

3 votes

Answer:

x = -1/3 and x = 3

Explanation:

I'm not sure, but I think you mean 3x^2 - 8x - 3 = 0

In that case:

1. Add 3 on both sides

3x^2 - 8x -3 + 3 = 3 -> 3x^2 - 8x = 3

2. Divide both sides by 3

x^2 - 8/3x = 1

3. Add ((8/3)/2)^2 to both sides

x^2 - 8/3x + ((8/3)/2)^2 = 1 + ((8/3)/2)^2

4. Simplify

x^2 - 8/3x + (4/3)^2 = 1 + (4/3)^2

x^2 - 8/3x + 16/9 = 1 + 16/9

5. Rewrite x^2 - 8/3x + 16/9 = 1 + 16/9 as a perfect square

and simplify 1 + 16/9

(x - 4/3)^2 = 25/9

6. Find the square root of both sides


√( (x -4/3)^2) = √(25/9)

7. Simplify

(x - 4/3) = ±5/3

8. Rewrite the equation as two seperate equations

(x - 4/3) = ±5/3 ->

a. (x - 4/3) = 5/3

b. (x - 4/3) = -5/3

9. Solve for x by isolating the variable (add 4/3 to both sides)

a. x = 5/3 + 4/3

b. x = - 5/3 + 4/3

10. Simplify

a. x = 9/3 -> x = 3

b. x = -1/3

User Seidah
by
6.2k points